Electronic and magnetic properties of EuNi2−δSb2 structural variants. (11th May 2020) - Nelson, W L; Jayasinghe, A S; Graf, D; Latturner, S; Baumbach, R E
Abstract: X-ray diffraction, magnetic susceptibility, magnetization, heat capacity and electrical resistivity results are reported for single crystals of two structural variants of EuNi2− δ Sb2 that crystallize in the CaBe2 Ge2 and ThCr2 Si2 -type structures. While the former occurs with a stoichiometric ratio, the latter exhibits a Ni site vacancy ( δ = 0.36). Both systems exhibit similar magnetic behavior at elevated temperatures, where there is an isotropic Curie–Weiss temperature dependence that indicates an antiferromagnetic exchange interaction between divalent europium ions, although it is stronger for the CaBe2 Ge2 -variant. At low temperatures, the differing structural environments that surround the Eu ions result in distinct ordering behavior. The CaBe2 Ge2 -variant orders antiferromagnetically near T N1 = 6.9 K and then undergoes a first order phase transition at T M = 4.6 K. The ThCr2 Si2 -variant exhibits simpler behavior, with antiferromagnetic ordering at T N2 = 5.6 K. For both compounds, an applied magnetic field suppresses the ordering temperatures and induce metamagnetic phase transitions, while applied pressure causes the ordering temperatures to increase. From these results, EuNi2− δ Sb2 emerges as a useful system in which to study the impact of structural variation on magnetism in a Eu-based metal.